1981
DOI: 10.1093/jn/111.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency in the Cat

Abstract: Two experiments were conducted to produce Zn deficiency in, and to establish approximate Zn requirements of, the cat. In experiment 1, soy protein (SP)-based diets were fed for 8 months: diet 1, basal, without added Zn, 15 ppm; diet 2, basal, 15 ppm Zn plus 2% CaHPO4; and diet 3, basal with added Zn, 67 ppm. Gross Zn deficiency symptoms were not observed, although spermatogenesis in cats fed diets 1 and 2 was abnormal. There were no differences in food intake or growth rate between treatments. Mean plasma zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Other skin disorders such as erythema, alopecia, pyoderma, scale, and crust had not shown in the studied cats (Watson 1998). Lowered zinc levels reported in this study are comparable to those found in research of Kane et al (1981). To this end, the monitoring of trace element concentrations especially with treatment opportunity may be helpful to clarify the reason of alterations in trace elements in cats with excessive shedding.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Other skin disorders such as erythema, alopecia, pyoderma, scale, and crust had not shown in the studied cats (Watson 1998). Lowered zinc levels reported in this study are comparable to those found in research of Kane et al (1981). To this end, the monitoring of trace element concentrations especially with treatment opportunity may be helpful to clarify the reason of alterations in trace elements in cats with excessive shedding.…”
Section: Discussionsupporting
confidence: 76%
“…A poorly formulated cat food has been known to cause mineral deficiency in cats (Watson 1998). In kittens, dietary zinc deficiency was reported to cause thinning of the haircoat, slow hair growth, scaly skin, and ulceration of the buccal margins (Kane et al 1981). Normal zinc concentrations are 75-120 μg/dl, with values less than 46 μg/dl considered zinc absolute deficiency (Tilley and Smith 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1930s, it was discovered that zinc was essential for life, growth, and reproduction in animals. In the 1950s, the syndrome of porcine parakeratosis was attributed to zinc deficiency and studies were published on experimentally produced syndromes of zinc deficiency in dogs in 1963, 1 and in cats in 1981 2 . Minimum dietary requirements have been established and are continuing to be revised for zinc and other trace elements in dogs and cats 3,4…”
Section: Introductionmentioning
confidence: 99%
“…It is important for normal carbohydrate, lipid, protein, and nucleic acid metabolism, and it is necessary for the maintenance of epidermal integrity, taste acuity, and immunological functions. [61][62][63] Clinical signs that are common to most species include growth retardation, abnormalities in hair and skin condition, gastrointestinal disturbances, and impaired reproductive performance. It is also a cofactor for ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) polymerases, making it an important mineral for rapidly dividing cells, such as those found in the skin.…”
Section: Zincmentioning
confidence: 99%